The skills that matter : teaching interpersonal and intrapersonal competencies in any classroom - Noonan, Patricia M.; Erickson, Amy S. Gaumer (Thousand Oaks : Corwin, 2018)
Build skills for lifelong success Many students leave high school without the skills they need to succeed in postsecondary education and the workforce. How can we better equip students for lifelong success? Research demonstrates that intrapersonal and interpersonal competencies impact student behavior and achievement, increase graduation rates, and promote strong post-school outcomes. The Skills That Matter provides middle and high school educators with the resources, tools, and practical examples to teach key intrapersonal and interpersonal competencies, including self-regulation, goal-setting, self-efficacy, assertiveness, and conflict management. Readers will find Competency-specific evidence-based instructional strategies with examples, and Tools such as sample instructional plans, formative assessments, and student-friendly products. This book provides teachers with the practical information they need to better develop socially and emotionally engaged, career-equipped, lifelong learners.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Affective education -- United States; Interpersonal relations -- Study and teaching -- United States; Social skills -- Study and teaching -- United States; Self-efficacy.; Self-control.; Goal (Psychology); Assertiveness (Psychology); Conflict management